Numerical Analysis Of Stacking Sequence In Frp Laminate Under Dynamic Resin Behavior. (2019) - Saravanan, W.S.R.; Krishnamoorthy, A.; Manigandan, S.; Gunasekar, P.
Abstract: Composite materials intriguing with numerous applications in all industrial sectors. In this project we investigate the effect of the multioriented stacking sequence optimization of the laminated structure. The stacking sequence is done by arranging the fibers at singlet orientation based on their mechanical strength review of different fibers. We have taken four different types of fibers like glass, Basalt, Kevlar, Jute to form a laminate of identical orientation of 30, 60 and 90 degrees. These fibers are arranged in the order of (30/30/30/30) s (60/60/60/60) s and (90/90/90/90) s to form a laminate. The hybrid composites we are fabricated using a hand layup process under compression type with infusion of epoxy resin. The results of the ordinary optimized laminate are compared and the efficiency of the optimization is calculated based on standard properties. We also investigate the flexural strength of the fiber and we visualize the micrographs structure of plastic strain at three different orientation. We also investigated the effect of different stacking sequences of glass, Kevlar, natural and basalt fabrics on the flexural properties of hybrid composite laminates.. Three-point bending test was performed and the fracture surfaces were examined by scanning electron microscopy. Tensile and compressive test also done on the laminate to find the enhanced mechanical properties. Cohesive behavior also investigated (Surface to surface interaction). In addition to the experimental evaluation, numerical simulation is done using Abaqus FEA tool. Numeric and experimental results are compared with each other for validation and to yield the optimized results.